A new lightweight authentication protocol in IoT environment for RFID tags - radan, Alireza; samimi, Hoseine; moeni, Ali (International Journal of Engineering and Technology, 2018)
Nowadays, internet of things (IoT) is a prominent technology that provides the field for connection and information transfer through communicational networks like internet and intranet. Since IoT is applied in various functions so that personal information of individuals or objects may be read without consent of them or in absence of a secure protocol, that is a challenge in this part, this study aimed at identifying tags efficiently in order to protect privacy of things against attackers. In this research, a two-factor authentication protocol based on the public key cryptography has been presented in order to protect privacy. It has been tried in this protocol to diminish complicated calculations while the proposed method can resist against some attacks like tampering with tag and tag reader, tag tracking, man-in-the-middle attack, and replay attack. To examine the proposed method, application of paying toll in traffic management was used. Various traffic models have been considered to pay toll in proposed model and implementation of this method was done in simulation environment of MATLAB. In this simulation, two cryptography algorithms with Robin and ECC public keys with keys in different sizes were evaluated and results showed that almost all of passed tags were identified using an anticipation rate with high rate between tag and tag reader in a system implemented with Rabin algorithm. Moreover, this ratio was higher than 90% in a system that was implemented with ECC algorithm. However, application of conventional symmetric cryptographic algorithms such as AES can reduce ratio of read tags to lower than 20%. Â Â Â